1999
DOI: 10.1515/jpm.1999.043
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic role of "in utero” magnetic resonance imaging

Abstract: Satisfactory imaging was obtained in all but one case. In order to define the "reliability" of MRI for a given condition, a diagnostic score was designed and separately given by the obstetrician and the radiologist involved in the case. MRI scored less than ultrasonography for abnormalities of the fetal contour and for large and complex distortion of the CNS as holoprosencephaly. For subtle midbrain anomalies, as well as for neuronal migration disorders, MRI definitely was superior to sonography. For other ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 15 publications
(9 reference statements)
1
11
0
Order By: Relevance
“…In 10-25% of the cases, even in experienced hands, associated anomalies are not detected by US [20]. In some of those cases the US is not able to detect for example migration disorders or corpus callosum agenesis [7,[22][23]. In other cases, technical problems, like obesity or oligohydramnios, are the reason for failing in making a correct diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In 10-25% of the cases, even in experienced hands, associated anomalies are not detected by US [20]. In some of those cases the US is not able to detect for example migration disorders or corpus callosum agenesis [7,[22][23]. In other cases, technical problems, like obesity or oligohydramnios, are the reason for failing in making a correct diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that in cases in which the sonographic diagnosis is unclear, MR examinations can provide important anatomic information that aids in diagnosis, parental counseling, planning delivery, and perinatal surgical procedures (86,(95)(96)(97)(98). In particular, MR can be helpful in assessment of sacrococcygeal teratoma.…”
Section: Non-cns Anomaliesmentioning
confidence: 99%
“…Disagreement was noted mainly for midline anomalies (48.6%) [21]. In another study of 92 patients, MRI diagnosed more anomalies in fetal brain, thorax, abdomen, and skeletal systems [22]. Some studies have confirmed this superiority of MRI [2,22].…”
Section: Indications Of Fetal Mrimentioning
confidence: 95%
“…In another study of 92 patients, MRI diagnosed more anomalies in fetal brain, thorax, abdomen, and skeletal systems [22]. Some studies have confirmed this superiority of MRI [2,22]. These studies were, however, criticized for their inherent biases, such as their retrospective nature, skill of ultrasound examiners, and time lapse between ultrasound and MRI that may allow for some in utero evolution of the lesions.…”
Section: Indications Of Fetal Mrimentioning
confidence: 99%